Transnationalism in Mozambican literature : the case of Glória de Sant'Ana - Plaetse, Aagje Vander (2019)
This thesis discusses transnationalism in literature from two perspectives: theoretical and practical. In the first part of this thesis, a theoretical background is given of this concept, starting from transnationalism as a consequence of the general phenomenon of globalization, then as a movement within literature, and finally as a phenomenon within poetry specifically. It is argued that transnational literature is a specific subset of world literature, with the main difference between the two being found in their respective relationships with the national literary circuit: where (non-transnational) world literature is still very much dependent on and affiliated with national literature, transnational literature often cannot be unambiguously affiliated with any nation’s literary tradition. It is also argued that more awareness of transnationalism is needed within the field of literary criticism. In the second part of this thesis, transnationalism is investigated from a practical perspective as an element in Glória de Sant’Anna’s work. A corpus of this transnational poet’s intimate lyricist work is analysed and characteristic transnational traits are identified and discussed. These traits include: a deep struggle with identity (and the fluid identity which the transnational lyrical subject adopts as a result of this struggle), transnational suffering (different forms of pain inherent to the transnational existence) and the sea as a vehicle for various transnational symbols (including the ship, the maritime voyage, shipwrecks, and the substance of water itself).